2023
DOI: 10.1177/00031348231175490
|View full text |Cite
|
Sign up to set email alerts
|

Current Controversies in the Management of Locally Advanced Colon Cancer

Abstract: n/a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Radiological staging was also found to be an independent predictor of long-term survival and was recommended for selecting patients with CC participating in clinical trials with NAC [42]. Magnetic resonance imaging allows a better soft tissue discrimination and diffusion-weighted imaging and may become an interesting complementary tool for the selection of patients [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiological staging was also found to be an independent predictor of long-term survival and was recommended for selecting patients with CC participating in clinical trials with NAC [42]. Magnetic resonance imaging allows a better soft tissue discrimination and diffusion-weighted imaging and may become an interesting complementary tool for the selection of patients [44].…”
Section: Discussionmentioning
confidence: 99%
“…This study also highlights the importance of a multidisciplinary committee [56]. Recent meta-analyses have indicated that neoadjuvant treatment improves long-term surgical and oncological outcomes [28,57,58]; but the final role of NAC in LACC in the therapeutic guidelines remains unresolved [24,44,[59][60][61][62]. This is the reason…”
Section: Discussionmentioning
confidence: 99%
“…These factors could potentially influence a tumour’s response to NAC and have an impact on survival. A further consideration is the need for accurate radiological staging to accurately identify patients who are suitable candidates for NAC 48 , 49 . The exploration of novel radiological findings, such as the emerging small arteriole sign, warrants meticulous consideration 50 .…”
Section: Discussionmentioning
confidence: 99%